Fast and Cost‐Efficient 17O‐Isotopic Labeling of Carboxylic Groups in Biomolecules: From Free Amino Acids to Peptide Chains. Issue 10 (17th January 2023) - Špačková, Jessica; Goldberga, Ieva; Yadav, Rishit; Cazals, Guillaume; Lebrun, Aurélien; Verdié, Pascal; Métro, Thomas‐Xavier; Laurencin, Danielle
Abstract: 17 O NMR spectroscopy is a powerful technique, which can provide unique information regarding the structure and reactivity of biomolecules. However, the low natural abundance of 17 O (0.04 %) generally requires working with enriched samples, which are not easily accessible. Here, we present simple, fast and cost‐efficient 17 O‐enrichment strategies for amino acids and peptides by using mechanochemistry. First, five unprotected amino acids were enriched under ambient conditions, consuming only microliter amounts of costly labeled water, and producing pure molecules with enrichment levels up to ∼40 %, yields ∼60‐85 %, and no loss of optical purity. Subsequently, 17 O‐enriched Fmoc/ t Bu‐protected amino acids were produced on a 1 g/day scale with high enrichment levels. Lastly, a site‐selective 17 O‐labeling of carboxylic functions in peptide side‐chains was achieved for RGD and GRGDS peptides, with ∼28 % enrichment level. For all molecules, 17 O ssNMR spectra were recorded at 14.1 T in reasonable times, making this an important step forward for future NMR studies of biomolecules. Abstract : Fast, user‐friendly and cost‐efficient labeling strategies were developed for 17 O‐enrichment of free amino acids, Fmoc/ t Bu‐ protected amino acids (produced on 1 g/day scale) and peptide side‐chains (site‐selective labeling). 17 O‐Labeled biomolecules were reproducibly obtained pure, in high synthetic yields (up to 85 %), and with high enrichment levels (∼40 %).